Evidence of horizontal and vertical interactions in health care spending in the Philippines - Kelekar, Uma; Llanto, Gilberto
his article examines whether within a decentralized system of health care spending, local government units in developing countries have any incentive to compete with one another. The existence of spatial competition, whether horizontal or vertical, is tested in the case of Philippines using local government health expenditures data. Results indicate that health spending is characterized by a strong positive interaction between municipalities, consistent with the existence of a horizontal fiscal interaction. However, the results provide less support for the existence of vertical externalities, with the interaction of municipalities with provinces being positive and marginally significant.
In: Health Policy and Planning, 2015 v0l. 30 (7) page 853-62.
Keywords: Delivery of Health Care -- economics; Economic Competition -- statistics and numerical data; Financing, Government; Local Government -- Philippines